PENDAMPINGAN PENGEMBANGAN INSTRUMEN UJIAN ADAPTIVE UNTUK MENINGKATKAN PROFESIONAL GURU SMA NURUL IMAN ISLAMIC BOARDING SCHOOL – PARUNG KABUPATEN BOGOR - anan sutisna; Awaluddin Tjalla; Gaguk Margono; Iva Sarifah; Achmad Ridwan; Riyadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2024)
ABSTRACT Community service was conducted at the designated area of the Graduate Program, specifically at Yayasan Al-Ashriyyah Nurul Iman Islamic Boarding School in Parung, Bogor Regency. The topic focused on teacher professionalism, particularly regarding adaptive test assessment within the Merdeka Curriculum. Teachers are expected to be able to design adaptive assessment instruments to meet the demands of 21st-century learning. This issue aligns with the pedagogical competence that teachers must possess in designing and implementing learning assessments. The subjects of this community service consisted of 30 high school teachers from Nurul Iman Islamic Boarding School – Parung, Bogor Regency. The involved partners were the Bogor Regency Education Office, West Java Province, and the Principal of SMA Nurul Iman. The community service activities were carried out in the form of training assistance with the following materials: (1) concepts of adaptive assessment; (2) development of adaptive test assessment instruments; and (3) implementation of adaptive assessment instruments in learning. The outcomes of this community service included the following products: (a) adaptive test assessment instruments for social and science subjects; (b) publication of the activities in online media and a video on a YouTube channel; and (c) a partner recognition letter indicating an increase in partner empowerment concerning teacher professionalism in designing adaptive test instruments. Keywords: Teacher professionalism, adaptive test instrument development ABSTRAK Pengabdian kepada masyarakat di wilayah binaan Pascasarjana yaitu Yayasan Al-Ashriyyah Nurul Iman Islamic Boarding School Parung Kabupaten Bogor. Adapun topik profesionalisme guru khususnya tentang penilaian adaptive tes dalam kurikulum medeka guru harus mampu merancang instrumen penilaian adaptive, sehingga menyesuaikan dengan tuntutan pembelajaran abad 21. Permasalahan tersebut sejalan dengan kompetensi pedagogic yang harus dimiliki guru dalam merancang dan melaksanakan penilaian pembelajaran. Subyek pengabdian kepada masyarakat ini sebanyak 30 orang guru Sekolah Menengah Atas Nurul Iman Islamic Boarding School – Parung Kabupaten Bogor, dengan mitra yang terlibat adalah Dinas Pendidikan Kabupaten Bogor Propinsi Jawa Barat dan Kepala SMA Nurul Iman. Kegiatan pengabadian dilaksanakan dalam bentuk pendampingan pelatihan dengan materi tentang (1) konsepsi penilaian Adaptive; (2) pengembangan instrument penilaian adaptive test; dan (3) penerapan instrument penilaian adaptive dalam pembelajaran. Hasil kegiatan pengabdian kepada masyarakat tersebut berupa produk antara lain: (a) instrument penilaian adaptive test dalam pembelajaran sosial dan sain; (b) mempublikasi kegiatan di media online dan video pada saluran youtube dan (c) surat rekognisi mitra tentang adanya peningkatan keberdayaan mitra tentang profesionalitas guru dalam merancang instrument adaptive test. Kata kunci: Profesionalitas guru, pengembangan instrumen adaptive test